The Critical Choice of Animal Models in Nanomedicine Safety Assessment: A Lesson Learned From Hemoglobin-Based Oxygen Carriers - Bedőcs, Peter; Szebeni, János (Frontiers in Immunology, 2020)
Intravenous injection of nanopharmaceuticals can induce severe hypersensitivity reactions (HSRs) resulting in anaphylactic shock in a small percentage of patients, a phenomenon explicitly reproducible in pigs. However, there is a debate in the literature on whether the pig model of HSRs can be used as a safety test for the prediction of severe adverse reactions in humans. Given the importance of using appropriate animal models for toxicity/safety testing, the choice of the right species and model is a critical decision. In order to facilitate the decision process and to expand the relevant information regarding the pig or no pig dilemma, this review examines an ill-fated clinical development program conducted by Baxter Corporation in the United States 24 years ago, when HemeAssist, a diaspirin crosslinked hemoglobin-based O2 carrier (HBOC) was tested in trauma patients. The study showed increased mortality in the treatment group relative to controls and had to be stopped. This disappointing result had far-reaching consequences and contributed to the setback in blood substitute research ever since. Importantly, the increased mortality of trauma patients was predicted in pig experiments conducted by US Army scientists, yet they were considered irrelevant to humans. Here we highlight that the underlying cause of hemoglobin-induced aggravation of hemorrhagic shock and severe HSRs have a common pathomechanism: cardiovascular distress due to vasoconstrictive effects of hemoglobin (Hb) and reactogenic nanomedicines, manifested, among others, in pulmonary hypertension. The main difference is that in the case of Hb this effect is due to NO-binding, while nanomedicines can trigger the release of proinflammatory mediators. Because of the higher sensitivity of cloven-hoof animals to this kind of cardiopulmonary distress compared to rodents, these reactions can be better reproduced in pigs than in murine or rat models. When deciding on the battery of tests and the appropriate models to identify the potential hazard for nanomedicine-induced severe HSR, the pros and cons of the various species must be considered carefully.